The study of structural features of N- and O-derivatives of 4,5-dihydroxyimidazolidine-2-thione by NMR spectroscopy and quantum chemical calculations - Kalichkina, Liudmila E.; Fateev, Alexander V.; Krivolapenko, Polina K.; Isakova, Kristina A.; Knyazev, Alexey S. 1978-; Malkov, Victor S.; Bakibaev, Abdigali A.; Tuguldurova, Vera P. (Magnetochemistry)
In the present work the new N-methylol and O-alkyl derivatives of 4,5-dihydroxyimidazolidine-2-thione (DHIT) are synthesized. The effect of N-alkyl, N-phenyl, N-methylol, and O-alkyl substituents of DHIT on the 13C, 1H signals in NMR spectra of the imidazolidine-2-thione ring is systematized using quantum-chemical calculations. The shift values of carbon and hydrogen atoms are specific for the geometric isomers of the indicated DHIT derivatives. The chemical shifts of the carbon atoms of the methine groups allow identifying the cis- and trans-isomers of the N-alkyl derivatives of DHIT due to the upfield shifts of the cis-isomers. The introduction of an alkyl substituent at the N-position of the imidazolidine-2-thione ring leads to the upfield shifts of the carbon atoms of the ring due to the inductive effects of these groups. The ring current effect in the N-phenyl derivatives of DHIT that affects the positions of the carbon signals of the imidazolidine-2-thione ring has been found. The N-methylol derivatives of 4,5-dihydroxyimidazolidine-2-thione has been identified for the first time using 1D and 2D NMR.